Inflammatory bowel disease and Helicobacter pylori infection - Ming-Ming ZHU; Zhi-Hua RAN (Yixue xinzhi zazhi, 2022)
In recent years, there are different conclusions about the relationship between Helico-bacter pylori (HP) infection and inflammatory bowel disease (IBD), but most preclinical and retrospec-tive studies report that there is a negative association between HP and IBD. HP infection may reduce the risk of developing IBD. It is considered that this negative association is related to the history of the use of sulfasalazine and antibiotics, the immunomodulatory characteristics of HP and environmental factors. However, whether there is a direct causal relationship between the increased incidence of IBD and HP eradication is still uncertain. Although HP infection should be treated with eradication therapy, routine eradication of HP should be undertaken with caution for IBD patients or IBD susceptible gene carriers. The association between HP infection and IBD as well as the mechanism, and the development of IBD after eradication of HP will be discussed in this paper.